The impacts of macroeconomic risk factors on industrial stock returns in UAE and USA - Ali Rashed Alyammahi, Maryam (2021)
The effect of risk factors on equity markets plays a crucial role in formulating risk management strategies by market participants. Numerous studies in this area of research suggest different sets of factors that are thought to affect asset returns. Capital Asset Pricing Model (CAPM) theorists consider the market index to be the only relevant factor in measuring an asset’s systematic risk. However, many empirical studies based on CAPM fail to provide evidence for the relationship between the stock return and market beta across country. Hence, researchers looked for other risk factors. The arbitrage pricing theory (APT) as an alternative to the CAPM hypothesizes that asset returns are dependent on several types of risk factors. However, APT also fails to identify the relevant factor structure that can explain the variations in stock returns. Therefore, researchers looked for other risk factors. The purpose of this study is to examine the effect of local and global macroeconomic risk factors on the industries stock returns across national equity of two countries namely UAE and USA. The study employed a multifactor pricing model and single factor model is used to test the effect of global risk factors represented by the world market index on industries stock returns across seven industries in both countries. The industries derived from Securities and Committees Authority (SCA) in the UAE and Global Finance Data (GFD) data base were chosen. The data for the industry indices covers the period of May 2003 to May 2018. The findings showed that the effect of macroeconomic factor such as exchange rate, export, import, industrial production, inflation, money supply M1, money supply M2, and oil prices are varied across industries in both countries. The results also showed that global risk factor has stronger effect on industries’ return in both countries. Multifactor model show that local risk factors have a strong explanatory power in explaining the variations of the monthly industries excess return in these two countries. Significant relationships have been found between macroeconomic risk factors and industry stock returns in the two national markets, some factors have a uniform effect across industries, while others do not. However, the local market excess return is considered as the most important explanatory factor among local risk factors and the single factor model show that global risk factors as represented by the world market portfolio poorly explained the variations of the monthly excess returns. Finally, a practical perspective can be beneficial to the cross- country investors and practitioners in having better understanding of how and to what extent risk factors affect investment returns of different industries across countries. Such understanding should enable investors and practitioners to be more informed with respect to allocating, timing, and diversifying their international investment portfolios.